Adversity Quotient pada Siswa Tunanetra dalam Meningkatkan Literasi - Rory Ramayanti; Agung Iranda (UIN Sunan Kalijaga, 2022)
Obstacles in visionary function in blind student impacts on limitedlearning process, mainly in literacy activities such as reading, writing, andcounting. In preventing such obstacles, they need adversity quotient forenhancing literacy skill at school. Adversity quotient is very important sothat they could get through the difficulties in the process, not depend ontheir parent and teacher to counter society’s stigma on the issues, likesnormal student. The objective of research is to explore the meaning ofadversity quotient on blind student in improving their literacy.This studyused a qualitative method with phenomenological approach. Four blindstudents who study in Special Needs School of Prof. Sri Soedewi Jambibecame the subject of this study. Data collecting was carried out throughin-depth semi-structured interviews. An interpretative phenomenologicalanalysis was used as the data analysis technique. Study results indicate thatthe adversity quotients of blind students in improving literacy skillsencompass origin and ownership, motivation, perseverance, independence,and control. Factors affecting adversity quotients include parentalencouragement, social support, facilities, and future orientation.Abstrak. Hambatan fungsi penglihatan pada siswa tunanetra berdampakpada keterbatasan dalam proses pembelajaran, terutama pada aktivitasliterasi seperti membaca, menulis, dan berhitung. Dalam mengatasihambatan tersebut mereka membutuhkan kecerdasan daya juang (adversityquotinet) untuk meningkatkan kemampuan literasi di sekolah. Daya juangsangat penting agar mereka mampu mengatasi berbagai kesulitan dalammembaca, tidak bergantung pada orang tua dan guru, serta mengubahstigma masyarakat bahwa mereka tidak mampu belajar di sekolah sepertisiswa normal. Tujuan penelitian ini untuk menggali makna adversityquotient pada siswa tunantera dalam meningkatkan kemampuan literasi.Penelitian ini menggunakan metode kualitatif dengan pendekatanfenomenologi, subjek penelitian ini adalah siswa tunanetra yang menuntutilmu di Sekolah Luar Biasa (SLB) Prof. Sri Soedewi Jambi sebanyakempat orang, pengumpulan data dilakukan dengan wawancara semistruktursecara mendalam. Teknik analisis data menggunakan interpretativephenomenological analysis. Hasil penelitian menunjukkan bahwa adversityquotient siswa tunanetra dalam meningkatkan kemampuan literasi berupamengatasi kesulitan, motivasi, ketekunan, kemandirian, dan kontrol.Adapun faktor yang memengaruhi adversity quetiont yaitu dorongan orangtua, dukungan sosial, fasilitas, dan orientasi masa depan.